The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/bcr-2018-228763
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea in a patient with chronic lymphocytic leukaemia

Abstract: A 69-year-old Caucasian woman presented with chronic lymphocytic leukaemia (CLL; stage 1-Rai System), significant oropharyngeal lymphoid enlargement, snoring and fatigue. Overnight polysomnography revealed moderately severe obstructive sleep apnoea (OSA), which was managed successfully with oral appliance therapy with resolution of snoring and daytime fatigue. Structural abnormalities of the upper airways are known to cause OSA. Airway narrowing can result from bony structural abnormalities, nasopharyngeal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Another percentage, 86.98%, was reported by Iida-Kondo et al 34 A relatively large tongue in a normal-sized oral cavity or a normal-sized tongue in a small oral cavity can induce airway blockage by moving posteriorly. 1 35 This aligns with Rana et al, 1 who reported that the volume of the tongue and oral cavity may relate to that of the upper airway. The study explained that the ratio of tongue volume to oral cavity volume was negatively correlated with the volume of the oropharynx, which means that if the tongue volume increases while the oral cavity volume remains constant, the oral cavity cannot accommodate the increase and the tongue moves posteriorly, causing the volume of the oropharyngeal canal to decrease.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Another percentage, 86.98%, was reported by Iida-Kondo et al 34 A relatively large tongue in a normal-sized oral cavity or a normal-sized tongue in a small oral cavity can induce airway blockage by moving posteriorly. 1 35 This aligns with Rana et al, 1 who reported that the volume of the tongue and oral cavity may relate to that of the upper airway. The study explained that the ratio of tongue volume to oral cavity volume was negatively correlated with the volume of the oropharynx, which means that if the tongue volume increases while the oral cavity volume remains constant, the oral cavity cannot accommodate the increase and the tongue moves posteriorly, causing the volume of the oropharyngeal canal to decrease.…”
Section: Discussionsupporting
confidence: 84%
“…Upper airway collapse during sleep, also known as obstructive sleep apnea, is a disorder in which breathing stops intermittently and repeatedly for 10 seconds or more during sleep. 19 35 The cause depends on the part of the upper respiratory tract that is affected; when it is the posterior part of the tongue, the tongue muscles relax during sleep and the tongue falls backward, blocking the airway. 35 Mouhanna-Fattal et al 24 found that the oral cavity volume in participants with obstructive sleep apnea did not differ significantly from that in the control group, but the upper respiratory tract volume was smaller in the apnea group, indicating upper respiratory tract obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation